Wnt Signaling Deregulation in the Aging and Alzheimer’s Brain - Palomer, Ernest; Buechler, Johanna; Salinas, Patricia C. (Frontiers in Cellular Neuroscience, 2019)
ABSTRACT Growing evidence suggests that synaptic signalling is compromised in the ageing brain and in Alzheimer’s disease (AD), contributing to synaptic decline. Wnt signalling is a prominent pathway at the synapse and is required for synaptic plasticity and maintenance in the adult brain. In this review, we summarise the current knowledge on deregulation of Wnt signalling in the context of ageing and AD. Emerging studies suggest that enhancing Wnt signalling could boost synaptic function during ageing, and ameliorate synaptic pathology in AD. Although further research is needed to determine the precise contribution of deficient Wnt signalling to AD pathogenesis, targeting Wnt signalling components may provide novel therapeutic avenues for synapse protection or restoration in the brain.